Meningkatkan Hasil Belajar Siswa Kelas VII Melalui Metode Index Card Materi Nun Sukun dan Tanwin Di SMPN 1 Seruyan Hilir Timur - Ajimah Suja, Nema (MADINAH, 2022)
This study departs from the findings of researchers related to PAI learning in class VII which did not raise the interest of students so that it had an impact on student learning outcomes. Based on these problems, this study conducted a trial of the Index Card Match method which was considered effective in improving learning outcomes and according to the type of PAI material about nun breadfruit and tanwin. This study uses the Research and Development method or classroom action research conducted at SMPN 1 Seruyan Hilir Timur in class VII. The results of this study indicate that the implementation of the ICM method is in accordance with the implementation syntax. Meanwhile, student learning outcomes have been shown to increase, which is indicated by the increase in mastery learning outcomes from cycle I to cycle II. The difference in the percentage of completeness reached 44%. This can be seen from the achievement of student scores which were originally below the KKM (70) to be more increased. In addition, the increase in learning outcomes is also shown by classical learning completeness of 91% in the second cycle which was originally only 47%. This drastic increase can occur when the teacher reflects on learning on the shortcomings obtained in the first cycle so that it can be corrected in the second cycle.